Prospective first‐trimester screening for trisomies by cell‐free DNA testing of maternal blood in twin pregnancy. (27th April 2016) - Sarno, L.; Revello, R.; Hanson, E.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objectives: First, to examine in twin pregnancies the performance of first‐trimester screening for fetal trisomies 21, 18 and 13 by cell‐free (cf) DNA testing of maternal blood and, second, to compare twin and singleton pregnancies regarding the distribution of fetal fraction of cfDNA and rate of failure to obtain a result. Methods: This was a prospective study in 438 twin and 10 698 singleton pregnancies undergoing screening for fetal trisomies by cfDNA testing at 10 + 0 to 13 + 6 weeks' gestation. Chromosome‐selective sequencing of cfDNA was used and, in twin pregnancies, an algorithm was applied that relies on the lower fetal fraction contributed by the two fetuses. Multivariate regression analysis was used to determine significant predictors of fetal fraction and a failed result. Results: In twin pregnancies, the median fetal fraction was lower (8.0% (interquartile range (IQR), 6.0–10.4%) vs 11.0% (IQR, 8.3–14.4%); P < 0.0001) and failure rate after first sampling was higher (9.4% vs 2.9%; P < 0.0001) compared to in singletons. Multivariate logistic regression analysis demonstrated that the risk of test failure increased with increasing maternal age and body mass index and decreased with fetal crown–rump length. The risk was increased in women of South Asian racial origin and in pregnancies conceived by in‐vitro fertilization (IVF). The main contributor to the higher rate of failure in twins was conception by IVF which was observed in 9.5% of singletons and 56.2% of twins. In the 417 twin pregnancies with a cfDNA result after first or second sampling, the detection rate was 100% (8/8) for trisomy 21 and 60% (3/5) for trisomies 18 or 13, at a false‐positive rate (FPR) of 0.25% (1/404). In the 10 530 singleton pregnancies with a cfDNA result after first or second sampling, the detection rate was 98.7% (156/158) for trisomy 21 and 80.3% (49/61) for trisomies 18 or 13, at a FPR of 0.22% (23/10 311). Conclusions: In twin pregnancies undergoing first‐trimester screening for trisomies by cfDNA testing, the fetal fraction is lower and failure rate higher compared to in singletons. The number of trisomic twin pregnancies examined was too small for an accurate assessment of performance of screening, but it may be similar to that in singleton pregnancies. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.